Monuments as “Sites of Memory”: remembering the forgotten Ottoman past of the modern Turkish republic through Elif Shafak’s the architect’s apprentice - Sharma, Nancy; Jha, Smita (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article explores how monuments must not be seen as independent or self-referential depositories of historical knowledge; instead, they must be considered highly significant historical, cultural and socio-political artefacts “with important political implications” (Bozdogan, 2001, p. 12). Elif Shafak’s The Architect’s Apprentice (2015) establishes Ottoman monuments as the ‘sites of memory’ that have the potential to narrate alternative or buried histories. The present paper investigates how Shafak’s oeuvre helps revive the forgotten aspects of Ottoman Turkish heritage. It further delineates that these Ottoman monuments, as represented in the text, are nothing but the manifestations of the suppressed Ottoman heritage of the Republic of Turkey. The researcher attempts to undertake a close textual reading of the text by drawing insights from the conceptual framework of Pierre Nora’s idea of ‘sites of memory’ and the discourse concerning cultural memory and forgetting. The findings of this research reveal that Shafak’s oeuvre can be considered as a medium to understand how the imposition of ‘perpetual forgetfullness’ in the Modern Turkish Republic has defamiliarised the populace of the Republic from these Ottoman monuments, which are the material embodiments of the Ottoman memory and history. In this light, it becomes crucial to discuss these monuments as ‘sites of memory,’ for they have the potential to abridge the rupture between the forgotten Ottoman past and the Turkish present.